Reação de maracujazeiro amarelo a Meloidogyne Incognita Raça 3 - Garcia, Maria José de Marchi; Fischer, Ivan Herman; Bueno, C. J.; Almeida, Aparecida Marques de; Sampaio, Aloísio Costa [UNESP]; Wilcken, S.R.S. [UNESP]; Bertani, Rosemary Marques de Almeida (My University, 2011)
This study concerned the reaction of yellow passion fruit ‘Maguary’ and ‘Afruvec’ to the phytonematode Meloidogyne incognita race 3 in greenhouse conditions. An entirely randomized experimental design with 3 treatments (‘Maguary’, ‘Afruvec’, and tomato cv. ‘Rutgers’) and 4 repetitions was used, each plot consisting of 1 vase containing 1 plant. After 6 months, an evaluation was made of the index of galls and egg mass in the yellow passion fruit varieties and in the tomato cv. ‘Rutgers’. The classification of resistance to the phytonematode was made by criterion of the reproduction factor (RF). ‘Maguary’ presented a zero index of galls and egg mass, while ‘Afruvec’ showed a low index of galls and egg mass in relation to the tomato cv. Rutgers. According to the RF, ‘Maguary’ was characterized as immune to the phytonematode, while ‘Afruvec’ was resistant, and the tomato cv. ‘Rutgers’ was susceptible.

Neste trabalho estudou-se a reação de maracujazeiro amarelo ‘Maguari’ e ‘Afruvec’ ao fitonematoide Meloidogyne incognita raça 3, em casa-de-vegetação. Adotou-se o delineamento inteiramente casualizado, com três tratamentos (Maguari, Afruvec e Tomateiro cv. Rutgers) e quatro repetições, sendo a parcela constituída por um vaso contendo uma planta. Após seis meses, avaliou-se o índice de galhas e de massa de ovos nas cultivares de maracujazeiro amarelo e no tomateiro cv. Rutgers. A classificação da resistência ao fitonematoide foi feita utilizando o critério do fator de reprodução (FR). A ‘Maguari’ apresentou zero de índice de galhas e de massa de ovos, enquanto que ‘Afruvec’ mostrou baixo índice de galhas e massa de ovos comparativamente com o tomateiro cv. Rutgers. De acordo com o FR, a ‘Maguari’ enquadrou-se como imune ao nematoide, sendo a ‘Afruvec’ resistente e o tomateiro cv. Rutgers como suscetível.
Keywords: Passiflora sp.; Root-knot nematodes; Resistance; Reproduction factor; Passiflora sp.; Nematoide de galhas; Resistência; Fator de reprodução